'Luteal coasting' after GnRH agonist trigger – individualized, HCG-based, progesterone-free luteal support in 'high responders': a case series. Issue 6 (December 2015) - Kol, Shahar; Breyzman, Tatiana; Segal, Linoy; Humaidan, Peter
Abstract: This study reports 21 IVF cases with excessive ovarian response, who received gonadotrophin-releasing hormone agonist (GnRHa) triggering for final oocyte maturation, followed by a human chorionic gonadotrophin (HCG)-based, progesterone-free, luteal support, individually timed ('luteal coasting') according to endogenous luteal progesterone concentrations. One patient developed a brief early-onset moderate ovarian hyperstimulation syndrome (OHSS) condition. Six clinical pregnancies were achieved, two of which have resulted in live births thus far. To further individualize the luteal phase support post GnRHa trigger, the same principle that holds for follicular coasting, used in the context of OHSS prevention, may be valid. Monitoring luteal progesterone concentrations from the day of oocyte retrieval, and administering a bolus of HCG (1500 IU) when the concentration drops significantly, seems to facilitate fresh embryo transfer, even in patients with excessive ovarian responses.